Buccinator myomucosal flap for the treatment of velopharyngeal insufficiency in patients with cleft palate and/or lip, - Denadai,Rafael (2018)
Abstract Introduction: The interpretation of the speech results obtained with the buccinator myomucosal flap in the treatment of velopharyngeal insufficiency in patients with cleft palate has been limited by the restriction in the number of patients and the time of postoperative follow-up. Objective: To evaluate the effect of the buccinator myomucosal flap on speech hypernasality in the treatment of patients with cleft palate and velopharyngeal insufficiency. Methods: Patients with repaired cleft palate (± lip) who were submitted to surgical correction of velopharyngeal insufficiency using the bilateral buccinator myomucosal flap were assessed. Hypernasality (scores 0 [absent], 1 [mild], 2 [moderate], or 3 [severe]) was analyzed by three evaluators by measuring the audiovisual records collected in early and late preoperative and postoperative periods (3 and 12 months, respectively). The values were considered significant for a 95% Confidence Interval (p < 0.05). Results: Thirty-seven patients with cleft palate (± lip) showing moderate (16.2%) or severe (83.8%) hypernasality in the preoperative period were included. Analyses of the late postoperative period showed that hypernasality (0.5 ± 0.7) was significantly (p < 0.05) lower than the hypernasality of the preoperative and recent postoperative periods (2.8 ± 0.4 and 1.7 ± 0.9, respectively). Conclusion: The buccinator myomucosal flap is effective in reducing/eliminating hypernasality in patients with cleft palate (± lip) and velopharyngeal insufficiency.